Percepções de egressos sobre a prática como componente curricular em um curso de licenciatura em Matemática - Danielli Ferreira Silva (2019)
Considering that perceptions are reflections on the lived experiences, the main objective of this research was to identify and to analyze the perceptions of graduates of a Mathematics Degree in relation to the repercussions of Practice as Curricular Component (PCC) for professional practice. In order to understand the concept of PCC, we bring elements about the history of teacher education in the country and a documentary analysis on laws and resolutions. We conducted a survey of research that had the PCC focus on Mathematics Education. We began the research by selecting the University institution to be investigated and analyzing the Pedagogical Project. We sought the names of students who graduated between 2012 and 2016 and entered after the year 2009, the year in which the hours of PCC were included. We were able to contact 73 graduates and send an online survey to select the graduates in teaching career. Of the 39 who answered, 23 were acting as math teachers and were invited to give us an interview. We followed up with nine collaborating whose interviews addressed the experiences in teacher education course and relationships with the profession. The analysis was built from excerpts of the interviews, in the light of the literature on teacher education. It was possible to identify and to analyze the perceptions of graduates about the PCC from the reflections on: identification with the teaching profession; the approximation of the University to the school; the learning about the teaching methodologies and about the pedagogical practice; and the mathematical knowledge. From the perceptions of the graduates we point out that the PCC in the course investigated involves a set of activities that can be characterized as planned and reflective practice, where mastery of content and how to transform it pedagogically are considered for teaching action in the school. Concerning the teacher education course, the graduates point out the disarticulation between content and method, between the specific and pedagogical content, between the academic formation and the professional practice and mainly between the mathematics prioritized in the course and the school mathematics. We identified from the research that despite the advances and efforts of the institution's Mathematics teacher trainers, the development of PCC activities is still insufficient to professional practice and to promote an identity for the Mathematics Degree.